(untitled) (Indonesian Journal of Science and Technology, 2025)
Optimization of the use of the Piper trilinear diagram was carried out by adding Lithium isotope systematics as a more accurate water-type analysis. The method used in this research is to analyze the Cl/Li ratio > 1000, δ7Li < 10 ‰, and Lithium concentration of groundwater, and then the results of the analysis are integrated into a Piper trilinear diagram. The research results show that Lithium isotope systematics (Cl/Li ratio < 1000, δ7Li < 10 ‰ and Li concentration) graph can be divided into 3 regions, namely geothermal water type has Cl/Li < 1000 and δ7Li < 10 ‰, then shallow groundwater which has Cl/Li > 1000 but δ7Li < 10 ‰ experienced natural contamination from geothermal waters, and fluid that has a Cl/Li ratio > 1000 and 10 ‰ > δ7Li > 20 ‰ is estimated to be shallow groundwater.